2005
DOI: 10.1175/jcli-3312.1
|View full text |Cite
|
Sign up to set email alerts
|

100-Year Return Value Estimates for Ocean Wind Speed and Significant Wave Height from the ERA-40 Data

Abstract: In this article global estimates of 100-yr return values of wind speed and significant wave height are presented. These estimates are based on the ECMWF 40-yr Re-Analysis (ERA-40) data and are linearly corrected using estimates based on buoy data. This correction is supported by global Topographic Ocean Experiment (TOPEX) altimeter data estimates. The calculation of return values is based on the peaksover-threshold method. The large amount of data used in this study provides evidence that the distributions of … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

14
180
3
3

Year Published

2011
2011
2015
2015

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 243 publications
(200 citation statements)
references
References 27 publications
14
180
3
3
Order By: Relevance
“…The ERA-40 wave data consist of 6-hourly global fields with a 1.58 3 1.58 grid resolution. Sterl and Caires (2005) produced a statistically corrected dataset of the ERA-40 significant wave height H s (CERA-40). The PC20 H s global fields are compared to the CERA-40.…”
Section: Validation Data: Reanalyses and Buoy Datamentioning
confidence: 99%
See 2 more Smart Citations
“…The ERA-40 wave data consist of 6-hourly global fields with a 1.58 3 1.58 grid resolution. Sterl and Caires (2005) produced a statistically corrected dataset of the ERA-40 significant wave height H s (CERA-40). The PC20 H s global fields are compared to the CERA-40.…”
Section: Validation Data: Reanalyses and Buoy Datamentioning
confidence: 99%
“…Analyses of recent and ongoing changes rely mostly on observations from voluntary observing ships (VOS) with known biases (e.g., Gulev et al 2003;Gulev and Grigorieva 2004) or on global wave datasets produced within wave reanalysis (e.g., Caires et al 2004;Sterl and Caires 2005;Caires and Sterl 2005;Caires et al 2005;Semedo et al 2011;Chawla et al 2011Chawla et al , 2013. Satellite altimetry combined with wave model hindcasts (e.g., Young 1999;Chen et al 2002) or only remote sensing data (Young et al 2011) have also been used for present-day global wave climate studies.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…The rationale, under these selections, demands the run length to be large enough to cover the time period required for the phenomenon to be fully developed. In previous offshore studies [14,15,24,[26][27][28][29][30], these values were found to vary from 24 to 60h.…”
Section: Repeat Steps 2-4 For All the Available (Annual) Time Seriesmentioning
confidence: 99%
“…Recent applications of the POT approach to analyse the extremes of ocean waves are presented in e.g. Caires and Sterl (2005) and Thevasiyani and Perera (2014).…”
Section: Introductionmentioning
confidence: 99%